Analytical study of some of the achieved angles of the final throwing stage and their relationship to achievement in the effectiveness of the advanced javelin throw - Abdulelah Salama, Omar; Abdulkareem Hameed, Jamal; Salah Raheem, Ziadoon (International Journal of Psychosocial Rehabilitation, 2020)
In many studies and research, researchers deal with the study of angles occurring in the various joints of the body during performance, and how the change in these angles can be linked to the educational and training principles of most mathematical skills in order to know the correct mechanical position of movement and thus achieve the best achievement depending on the angles, and the study aimed to know the proportion the contribution of angles achieved on the one hand and digital level on the one hand , and also to find out the correlation between them on the other hand, suppose researchers to a high contribution ratio between the angles achieved to the stage of shooting digital level players javelin throw young people, because the researchers used the descriptive approach in a manner correlation of relevance nature of the research, was Selection of the research sample by the intended method, and the number was (4) players from Diyala club For the sports season (2020-2021) and their ages were under 18 years old, and the research procedures included imaging procedures, tests and measurements used in the research, which included research variables measuring the angle of approach, thrust and momentary thrust at the moment of throwing, as well as the digital level. The field application was done on the research sample after conducting the experiment Exploratory.